Ratio for upper, middle and lower chest expansion in healthy Malaysian adults aged 20 to 40 years/ Khairul An’Am Ali Rahman, Natila Fazlina Mat Isa & Fatim Tahirah Mirza - Ali Rahman, Khairul An’Am; Mat Isa, Natila Fazlina; Mirza, Fatim Tahirah (Faculty of Health Sciences, Universiti Teknologi MARA, 2020)
Background: Assessment of chest expansion by using the cloth tape measurement (CTM) has been reported to have between moderate and strong measurement properties. The test is used as a routine assessment technique in cardiorespiratory physiotherapy and is taught in undergraduate physiotherapy course. However, it appears that the test was done quite differently between studies and interpreted in various ways among the clinicians. Purpose: To determine the ratio for upper, middle and lower chest expansion among adults aged 20 to 40 years and to investigate whether change in test position (sitting vs. standing) affects the upper, middle and lower chest expansion. Method: Students and staff at Faculty of Health Sciences, UiTM were approached to participate in this study. Anthropometric and demographic data were taken. Assessment of chest expansion was done using CTM at three landmarks (i.e. upper [2nd intercostal space], middle [4th intercostal space] and lower [xiphoid] chest). The measurement was taken three times in two positions (i.e. sitting and standing). Result: Mean chest expansion for all participants (n=212) in sitting and standing positions for upper, middle and lower chest were 3.3±1.4cm, 3.7±1.2cm, and 3.2±1.4cm (1.03:1.16:1; p>0.05), and 3.4±1.3cm, 3.5±2.4cm and 3.1±1.5cm (1.1:1.13:1; p>0.05), respectively. There was no significant different in expansion between upper, middle and lower chest in different test positions in all participants (p>0.05). Conclusion: Although middle chest has the biggest expansion, the expansion ratio between the other levels is about the same. There is not much change in chest expansion when measurement was taken in either sitting or standing.